SP600125, a JNK-Specific Inhibitor, Regulates in vitro Auricular Cartilage Regeneration by Promoting Cell Proliferation and Inhibiting Extracellular Matrix Metabolism - Zhang, Peiling; Liu, Yanqun; Jia, Litao; Ci, Zheng; Zhang, Wei; Liu, Yu; Chen, Jie; Cao, Yilin; Zhou, Guangdong (Frontiers in Cell and Developmental Biology, 2021)
In vitro construction is a major trend involved in cartilage regeneration and repair. Satisfactory in vitro cartilage regeneration depends on a suitable culture system. Current chondrogenic culture systems with a high content of transforming growth factor beta-1 effectively promote cartilaginous extracellular matrix (ECM) production but inhibit chondrocyte survival. As is known, inhibition of the c-Jun N-terminal kinase (JNK) signaling pathway acts in blocking the progression of osteoarthritis by reducing chondrocyte apoptosis and cartilage destruction. However, whether inhibiting JNK signaling resists the inhibitory effect of current chondrogenic medium on cell survival and affects in vitro auricular cartilage regeneration (including cell proliferation, ECM synthesis and degradation) has not been investigated. In order to address these issues and optimize the chondrogenic culture system, we generated a three-dimensional in vitro auricular cartilage regeneration model to investigate the effects of SP600125 (a JNK-specific inhibitor) on chondrocyte proliferation and ECM metabolism. SP600125 supplementation efficiently promoted cell proliferation at both cellular and tissue levels and canceled the negative effect of our chondrogenic culture system on cell survival. Moreover, it significantly inhibited ECM degradation by reducing the expressions of tumor necrosis factor-alfa, interleukin-1-beta and matrix metalloproteinase 13. In addition, SP600125 inhibited ECM synthesis at both cellular and tissue levels, but this could be canceled and even reversed by adding chondrogenic factors; yet this enabled a sufficient number of chondrocytes to be retained at the same time. Thus, SP600125 had a positive effect on in vitro auricular cartilage regeneration in terms of cell proliferation and ECM degradation but a negative effect on ECM synthesis which could be reversed by adding chondrogenic medium. Therefore, a combination of SP600125 and chondrogenic medium might help in optimizing current chondrogenic culture systems and achieve satisfactory in vitro cartilage regeneration by promoting cell proliferation, reducing ECM degradation, and enhancing ECM synthesis.